Exploring the Depths of Modern Life as Reflected in Franz Kafka’s The Metamorphosis - Uddin, Md Jashim (IUBAT Review, 2023)
This paper explores the philosophical themes present in Franz Kafka's seminal work, The Metamorphosis (1915). Through an analysis of the novella, the paper delves into how Kafka grapples with profound issues such as alienation, existential crisis, and the human condition. The paper examines the transformative journey of the protagonist, GregorSamsa, who undergoes a physical and psychological metamorphosis into a bug, serving as a metaphor for the human experience of feeling disconnected from oneself and others. By immersing readers in Gregor's surreal and isolating world, Kafka prompts introspection into the inherent struggles of human existence. Moreover, the paper explores Kafka's masterful use of absurdity and dark humor throughout the narrative, shedding light on the futility of human existence and the inevitability of death. By interweaving absurd and grimly humorous elements, Kafka offers a critique of societal norms and underscores the existential anxieties that arise when confronted with the absurdity of life. The pervasive sense of irony and bleakness in the novella serves to highlight the absurd and inherently flawed nature of the human condition. Furthermore, the research paper delves into the influences that shaped Kafka's philosophy, particularly his Jewish identity and experiences living in a rapidly changing, industrializing society. Kafka's writing reflects the anxieties and struggles of individuals in a modernized world, highlighting the existential dilemmas faced by those grappling with societal expectations and personal identity. By examining the philosophical dimensions of "The Metamorphosis," this paper offers a nuanced and in-depth analysis of Kafka's views on the human experience and the search for meaning in modern life. It invites readers to engage with the profound questions raised by Kafka's work and provides valuable insights into his philosophical stance. IUBAT Review, 6(2): 131-157